Digitised Maps in the Danish Map Collection - Lenschau-Teglers, Annie; Rønsberg, Vivi Gade (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
As in the rest of the library world, The Royal Library in Copenhagen is in the process of digitising its collections. At the moment we are mainly working on the handwritten manual catalogue - but digitising the material is also a major working assignment. The Map Collection at The Royal Library has today divided the effort in digitising its materials into 3 groups: 1. Digitised maps as a vital addition to the records in our bibliographic database REX 2. Digitised maps presented as a Digital Facsimile, accessible on our homepage. 3. Digitised maps taken out of its original contents and placed in a Virtual Exhibition also accessible on our homepage